Quantity Take Off Comparison Using Building Information Modelling (BIM) with Autodesk Revit Software and Traditional Method - Fredrick Jeremia Simatupang; Gina Cynthia Raphita Hasibuan; Indra Jaya; Syahrizal; Rezky Ariessa Dewi; Gea Geby Aurora Syafridon (Talenta Publisher, 2024)
Nowadays, the development of technological advances and information has grown rapidly in various aspects including the development of construction projects. One of the construction technology innovations is Building Information Modeling (BIM). Obstacles that are often or commonly encountered in the implementation of construction projects are delays or delays in work, rework, and inaccuracies in the calculation of the required quantity. The problems caused by conventional methods can be minimized by utilizing construction technology, namely BIM at the construction stage. This research aims to compare the volume of traditional (conventional methods) and BIM methods. This research uses a comparative research method and quantitative approach. In this research, a comparative analysis between conventional methods and BIM methods is carried out. Based on the data analysis that has been carried out, it is found that the BIM results are smaller than the conventional project results with a percentage comparison difference of 8.61% for the volume of concrete work, and 6% for the weight of reinforcement.